Theory and Practice of the Schengen Evaluation Mechanism - Balla, József (Magyar Rendészet, 2019)
The abolition of border controls executed at the internal borders of the European Union and the Schengen Area is one of the most significant acquis with regards to the freedom of movement. However, particular occasions or events allow to temporarily reintroduce border controls at the internal common border section of two Member States. This requires a properly trained and educated personnel, technology and infrastructure.